Growth performance, nutrient digestibility and carcass characteristics of goats fed different levels of palm oil decanter cake - Ahmed, Anwar Abdelgafar Shaban (2014)
Feed shortage in Malaysia is undeniably requires alternative potential local cheap feed sources to reduce the import costs. Introducing palm oil decanter cake (PODC) for ruminant ration to overcome feed shortage could help in this case, since PODC contains of crude protein (CP) 11.4-14%, locally produced in big amounts and cheap. However, researches investigating the chemical composition of PODC and the effects on growth performance and carcass characteristics in goats are limited; therefore the objectives of a series of experiments were to evaluate such effects. In the first experiment, two samples of PODC were collected from five different palm oil mills and subjected to proximate analysis. The chemical compositions of the PODC were significantly different between all mills (P < 0.05) and the mean were for the DM (dry matter), Ash, CP (crude protein), NDF (natural detergent fiber), ADF (acid detergent fiber) and ADL (acid detergent lignin) and EE (ether extract) were: 7.16, 16.47, 12.48, 50.39, 38.03, 38.03 and 12.26 respectively. In the second experiment 15 male one year Kacang goats with initial mean body weight (BW) of 16.2 ± 1.3 kg, the objective was to evaluate the nutrient digestibility and feed intake when fed with different levels of the PODC. The experiment duration was 30 days, including 9 days of adaptation period, 21 days of a feeding trial and the digestion trials was at the last 7 days of the feeding trial. The goats were fed Napier grass ad libtum and also received once daily (1.5% of BW) one of three concentrate diets (treatments; approximately 16% CP on dry matter basis), five goats were randomly assigned to each treatment. The treatments included (1) grass + PKC (T1, control) and PODC replaced partly the PKC at a level of (2) 10% decanter cake + grass, (T2) and (3) 20% decanter cake + grass (T3). The intake of grass was not affected by dietary treatments. However, the intake of PODC was significantly increased by increasing the level of PODC in the diet. Similarly, total dry matter intake was higher (P < 0.05) in goats fed with 10% or 20% respectively comparable to those fed control diet. Additionally, apparent digestibility of DM, OM, CP, EE, ADF and NDF were similar (P < 0.05) among dietary treatments T1, T2, T3 and T4. In the third experiment, twenty four one year male Kacang goats with initial mean body weight (BW) of 16.8 ± 1.14 kg been used. The objectives were to evaluate the effect of supplementation of different levels of PODC on growth performance and carcass characteristic of goats. The four treatments were: control diet consisting of soy bean meal (SBM) and corn grain (T1) or 10% (T2), 20% (T3), 30% (T4) PODC. All goats were fed Napier grass ad libitum and also received once daily (1.5% of BW) one of four concentrate diets (treatments; approximately 16% CP on dry matter basis). Total feed intake was similar (P < 0.05) in all groups, however, T3 and T4 had significantly higher (P<0.0001) PODC intake compare with T1 and T2. BW gain (kg), slaughter weight (kg), empty body weight (kg), hot carcass weight (kg), cold carcass weight (kg) and carcass dressing percentage were not significantly different (P < 0.05) among dietary treatments. It was concluded that PODC has variable chemical compositions and different from one mill to another. PODC could be used to replace grains in the rations of growing goats up to 30% with normal performance.